Dynamics of pasture discharge and its architecture - Gastó, Juan M. (International Center for Tropical Agriculture, 1993)
An analysis is presented of the relationships between the form of grazing land or pasture—a form that is expressed by its architecture in the ecosystem—and the dynamics of discharge in the pasture used by cattle. The objective of searching and demonstrating relationships of this nature is to establish a conceptual framework that will help the phytogeneticist make decisions on the improvement of species destined for pasture. The first part of this study analyzes pasture architecture with regard to the form of phytocoenosis and the design of improved forms. Also presented is a general function of architecture that allows a description of plant form. The second part of the study describes and compares diverse discharge models. These models are applicable to specific processes of a biotic and abiotic nature. From this background, one deduces a general function of pasture discharge that is analyzed in its turn as a forage flow from phytocoenosis to zoocoenosis. Some parameters related to discharge such as grazing intensity and use intensity, as well as ecological cost of the harvest, are included in the study. Finally, the discharge of an annual Mediterranean meadow is described as an example of the process.